Do empoderamento da representação direta dos trabalhadores - Baltazar, Vanessa Anitablian (2017)
The present dissertation has as main objective the development of a study on the direct representation of the workers, prescribed in article 11 of the Brazilian Constitution, both in society and in the work environment, addressing the social relevance of worker consciousness as a salutary measure in the improvement of labor relations. We bring models such as self-management and comanagement or democratic management, which deals with a differentiated format in which the collective of workers take part in the decision-making of the company. We delimit the prerogatives of each representative body in order to shape a peaceful relationship between unions and direct representation bodies. We demonstrate the modulation of ILO Convention n. 135, ratified by Brazil, and Recommendations ns. 143 and 130, on workers representation. We analyze the treatment of the issue in comparative law, bringing to the fore the regulation of direct representation of the French, Portuguese and Chilean legal systems. We present a comprehensive study on the legislative and jurisprudential evolution of direct representation in Brazil, emphasizing the peculiarities of the respective institutions in Brazilian legislation. Finally, we bring the importance of direct representation as a fundamental right of the worker, with a focus on legal and constitutional provisions, as well as propose a model of effective functioning of the institute